Discovering Islam : Making Sense of Muslim History and Society - Akbar S. Ahmed (London Routledge Taylor & Francis Group, 2002)
This accessible work balances the image of Islam as aggressive and fanatical with an objective picture of the main features of Muslim history and the compulsions of Muslim society
Include Maps and Index
Keywords: Islam -- Religions -- Islam--Social aspects